TOURISM QUALIFIED HUMAN RESOURCES: DIFFERENTIATION FACTORS IN TOURISM DEVELOPMENT POLES OF THE WEST AND OF LEIRIA-FATIMA - Eurico, Sofia Teixeira; da Silva, João Albino Matos; do Valle, Patrícia Oom (Tourism & Management Studies, 2012)
This paper examines the influence of contrasting elements that distinguish graduates in tourism as far as their professional life is concerned. The Tourism Development Poles of the West and of Leiria-Fatima are used as case studies. The recognition of the importance of human resources development in tourism, in line with the attention that studies in tourism have been achieving at the level of higher education, become more relevant if we consider the dynamism and constant metamorphosis of markets and socio-economic realities that characterize our days. This justifies the study of the contextualization of professional graduates in tourism for an assessment of the importance of different factors regarding more academic, socioeconomic or professional issues with influence in their careers. Through a univariate analysis, which allowed the characterization of the sample, and an inferential approach, which permitted to assess the relations between variables potentially differentiating of the individuals, we obtained results that assess the higher education graduates in tourism from different perspectives such as their academic in/success and their integration into the labor market. The results indicate that factors related to gender and age, with the frequency of post-graduate training, with the positions held and work experience prior to graduating influence the employment status of the individual